Paraneoplastic Pemphigus: A Case Report - Nidhi Shah; Rosina Paudel; Arpana Rijal (Nepal Journal of Dermatology, Venereology & Leprology)
Paraneoplastic pemphigus (PNP) is a rare autoimmune bullous disease associated with underlying neoplasms. Targetoid lesions, intractable stomatitis and refractory course of disease are some of the characteristic features of paraneoplastic pemphigus. It is usually associated with lymphoproliferative disorders, and rarely with solid tumors. We present a case of a 35 years old female with a six-months history of recurrent, severe, recalcitrant stomatitis and widespread blistering and erosions with involvement of palms and soles. A provisional diagnosis of PNP was made based on clinical features. Investigations for an underlying neoplasm revealed presence of solid lesion of size 6.7 x 6.4 cm in left adnexa, likely an ovarian tumor. PNP should be considered in the differential diagnoses in severe atypical mucocutaneous manifestations of pemphigus vulgaris and diagnostic screening for search for an underlying tumor should be performed.